(untitled) (Journal of Applied Learning and Teaching, 2022)
The COVID-19 pandemic had an impact on many facets of education and the education experience. This paper seeks to understand how it impacted the support in place for part-time, mature students studying at UCD College of Business. The concepts of learner-centredness and student engagement are explored in order to ask the question ‘How has the model of part-time student support provision evolved since the COVID-19 pandemic?’. The Dowling and Ryan (2007) model of student support was used as a heuristic to look at what principle changes are evident in the post-COVID19 environment. This case study demonstrates that the model of part-time student support has evolved since the Dowling and Ryan (2007) model as a result of changing student needs, the external pressures due to the pandemic, and the modes of provision now available to students. In particular, the proliferation of technology has changed the way students ultimately engage with their programme of study. Four central tenets of student support for part-time mature students were identified, namely: 1) Day to day support and use of technology; 2) Feedback and learner progress; 3) Skills Development and 4) Orientation and learner integration. Looking to the future, technology and learner support are fundamental to understanding and achieving learner-centred and engaging student support models. This paper’s reflection on the part-time student experience and how learner support might have been reshaped as a result of the pandemic will hopefully help to influence and shape policy-making in higher education and determine how practitioners provide support for part-time students. It also suggests the current concept of learner-centredness might also be expanded upon.